Towards Skillful Global Citizenship Education - Nguyen, Tram Truong Anh (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2013)
This article examines the implications of aspects of Buddhist philosophy for contemporary Global Citizenship Education. With primary reference to the writings of Thich Nhat Hanh, it specifically considers Buddhist understandings of suffering, the doctrine of no-self, the notion of store-consciousness, and the law of karma. The article subsequently introduces a skillful global citizenship education that is built on three pillars; namely, skillful awareness of interdependence, skillful compassion, and skillful awareness of intention.